Pengaruh Pengelolaan Keuangan, Digitalisasi Bisnis, dan Entrepreneurial Marketing Terhadap Keberlanjutan Usaha UMKM Sektor Perdagangan di Kecamatan Buleleng - Agustini, Ria; Suwena, Kadek Rai (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This research aims to determine the influence of financial management, business digitalization and entrepreneurial marketing on the sustainability of MSMEs in the trade sector in Buleleng District. In this study, the population used was 1,196 formal MSMEs in the trade sector in Buleleng District in 2023. The sampling technique used non-probability sampling with a purposive sampling technique and to determine the number of samples using the Slovin formula, so that a sample of 175 people was obtained. This research uses quantitative data with primary data sources obtained through questionnaires and secondary data obtained from MSME data in the trade sector in Buleleng District.The data analysis technique used is multiple linear regression analysis with partial (t test) and simultaneous (F test) hypothesis testing. The results of this research show that (1) financial management has a positive and significant effect on the sustainability of MSMEs in the trade sector in Buleleng District, (2) business digitalization has a positive and significant effect on the sustainability of MSMEs in the trade sector in Buleleng District, (3) entrepreneurial marketing has a positive and significant effect on the sustainability of MSMEs in the trade sector in Buleleng District and (4) financial management, business digitalization and entrepreneurial marketingsimultaneously have a positive and significant effect on the sustainability of MSMEs in the trade sector in Buleleng District.